Preparation method of formaldehyde adsorption antibacterial material with activated carbon as carrier

By modifying activated carbon fibers, including soaking alkaline and KMnO4 aqueous solutions, and processing in amine quinone network and silver solutions, the adsorption and antibacterial properties of activated carbon materials are improved, and the problems of poor adsorption ability and poor antibacterial effects of activated carbon adsorbent materials in the prior art are solved.

CN119500075APending Publication Date: 2025-02-25HENAN INST OF ENG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411525129.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, activated carbon adsorption materials have poor adsorption ability to small particulate matter and have poor antibacterial effect.

Method used

Modified activated carbon fibers are formed by soaking activated carbon fibers in alkaline solution and aqueous KMnO4 solution and treated in amine quinone network and silver solution to improve the adsorption and antibacterial properties of the material.

Benefits of technology

The adsorption ability and antibacterial effect of activated carbon materials on small particulate matter has been significantly improved, and the shortcomings of activated carbon adsorption materials in the prior art have been solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500075A_ABST
    Figure CN119500075A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a formaldehyde adsorption antibacterial material taking activated carbon as a carrier, activated carbon fibers are soaked in a potassium permanganate solution to generate manganese dioxide, then the manganese dioxide is soaked in an amine quinone network substance solution and a silver solution in sequence, and the high specific surface area and the porous structure of the manganese dioxide provide a large number of adsorption sites; the amine-quinone network and silver ions can improve the overall antibacterial ability of the material, and amino and quinonyl on the amine-quinone network can enhance the particle adsorbability of activated carbon through hydrogen bonds, Van der Waals force and the like, so that the defects of poor small particle adsorption ability and poor antibacterial effect of an activated carbon adsorption material in the prior art are overcome; the amine-containing compound is polyethyleneimine, the quinone-containing compound is 5-hydroxy-1, 4-naphthoquinone, the mixing mass ratio of the amine-containing compound to the quinone-containing compound is 1: 1, the amine-quinone network substance has a network structure, and the network structure can provide additional adsorption sites and enhance the adsorption capacity to small particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorption material preparation, and in particular to a method for preparing a formaldehyde adsorption antibacterial material using activated carbon as a carrier. Background Art

[0002] Activated carbon is a carbon material made from carbon-containing raw materials such as wood, coal or petroleum coke through pyrolysis and activation. It has a developed pore structure, a large specific surface area and abundant surface chemical groups. These characteristics make activated carbon have a strong adsorption capacity and can adsorb particulate matter and pollutant gases. The adsorption mechanism of activated carbon mainly includes physical adsorption and chemical adsorption. Physical adsorption refers to the formation of a physical adsorption layer on the surface of activated carbon by substance molecules, while chemical adsorption refers to the chemical bond between substance molecules and the surface of activated carbon. These two adsorption methods work together in the adsorption process of activated carbon, allowing activated carbon to adsorb a variety of harmful substances.

[0003] The adsorption performance of activated carbon is affected by its pore structure and surface chemical properties. When the pore size of activated carbon is large, the adsorption performance for small particles and small-volume polluted gases is poor. For example, formaldehyde cannot be effectively adsorbed. In addition, small-pore activated carbon has too much sediment during the adsorption process, which affects the adsorption effect and causes bacteria to grow.

[0004] Therefore, it is necessary to improve the activated carbon adsorption material in the prior art to solve the above problems. Summary of the invention

[0005] The present invention overcomes the shortcomings of the prior art and provides a method for preparing a formaldehyde adsorbing antibacterial material using activated carbon as a carrier, aiming to solve the defects of the activated carbon adsorbing material in the prior art, such as poor adsorption capacity of small particles and poor antibacterial effect.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a formaldehyde adsorption antibacterial material using activated carbon as a carrier, comprising the following steps:

[0007] S1: soaking the activated carbon fiber in an alkaline solution, taking it out, washing it, and then drying it to obtain a modified activated carbon fiber, soaking the modified activated carbon fiber in a KMnO4 aqueous solution for 1 hour, and then placing the activated carbon fiber and the KMnO4 aqueous solution in a reactor to react for 24 hours;

[0008] S2: taking out the activated carbon fiber in the reactor in S1 and washing it, and then drying it in an oven for 12 hours at a temperature of 100° C. to 140° C. to obtain a formaldehyde adsorbing activated carbon material;

[0009] S3: mixing the amine-containing compound and the quinone-containing compound for reaction for 1-2 hours to form an aminequinone network, preparing the aminequinone network into an aminequinone network solution, soaking the formaldehyde adsorption activated carbon material in S2 into the aminequinone network solution for 2-4 hours, taking out the material after soaking and drying it at room temperature for 12-16 hours to obtain a primary treatment adsorption material;

[0010] S4: adding the once treated adsorption material in S3 into the silver solution and stirring for 4 hours, drying and heating the solid matter to obtain a formaldehyde adsorption antibacterial material with activated carbon as a carrier.

[0011] In a preferred embodiment of the present invention, the alkaline solution in S1 can be a NaOH solution with a concentration of 1 M. The activated carbon fiber is immersed for 30 minutes, and the activated carbon fiber is cleaned before immersion.

[0012] In a preferred embodiment of the present invention, the reaction temperature in the reactor in S1 is 60°C.

[0013] In a preferred embodiment of the present invention, the concentration of the KMnO4 aqueous solution in which the modified activated carbon fiber is immersed is 0.03M-0.07M.

[0014] In a preferred embodiment of the present invention, the amine-containing compound in S3 is polyethyleneimine, the quinone-containing compound is 5-hydroxy-1,4-naphthoquinone, and the mixing mass ratio of the amine-containing compound to the quinone-containing compound is 1:1.

[0015] In a preferred embodiment of the present invention, the solvent of the amine quinone network solution in S3 is dimethyl sulfoxide, and the concentration of the amine quinone network solution is 0.01-0.1M.

[0016] In a preferred embodiment of the present invention, the preparation process of the silver solution in S4 is to dissolve AgNO3 in ammonia water, the mass fraction of AgNO3 in the silver solution is 0.5%, the concentration of ammonia water is 28wt.%, and the mass ratio of formaldehyde adsorption activated carbon material to silver solution is 1:100.

[0017] In a preferred embodiment of the present invention, the solid matter drying and heating process in S4 is to separate the solid matter and dry it at 100° C. for 1 hour and then heat treat it at 400° C. for 5 hours.

[0018] In order to achieve the above-mentioned purpose, the second technical solution adopted by the present invention is: a formaldehyde adsorption antibacterial material using activated carbon as a carrier.

[0019] To achieve the above object, the third set of technical solutions adopted by the present invention is: an air filter material, which comprises, in order according to the air flow transmission direction: a protective layer, a particle filter layer, a formaldehyde removal / antibacterial functional layer and a skeleton layer, wherein the protective layer, the particle filter layer, the formaldehyde removal / antibacterial functional layer and the skeleton layer are compounded by ultrasound;

[0020] The protective layer is made of PET spunbonded non-woven fabric with a gram weight of 15-25g / m 2 ;

[0021] The particle filter layer is made of PP melt-blown cotton with a gram weight of 25-40g / m 2 ;

[0022] The formaldehyde removal / antibacterial functional layer uses formaldehyde adsorption antibacterial material with activated carbon as the carrier, with a gram weight of 50-100g / m 2 ;

[0023] The skeleton layer is made of PET wet-laid non-woven fabric with a gram weight of 70-100g / m 2 .

[0024] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0025] (1) The present invention provides a method for preparing a formaldehyde adsorbing antibacterial material with activated carbon as a carrier. After the activated carbon fiber is immersed in a potassium permanganate solution to generate manganese dioxide, it is immersed in an amine quinone network solution and a silver solution in sequence. Compared with the formaldehyde adsorbing antibacterial material in the prior art, the high specific surface area and porous structure of manganese dioxide provide a large number of adsorption sites. The amine quinone network and silver ions can improve the overall antibacterial ability of the material, and the amino groups and quinone groups on the amine quinone network can enhance the particle adsorption of the activated carbon through hydrogen bonds and van der Waals forces, thereby solving the defects of the activated carbon adsorption material in the prior art, such as poor adsorption capacity for small particles and poor antibacterial effect.

[0026] (2) In the present invention, the reaction between the activated carbon fiber and the potassium permanganate solution in the reactor is a closed space reaction, which promotes the reaction between the activated carbon fiber and the potassium permanganate solution and can control the temperature and pressure of the reaction. Compared with the prior art, the reaction process of the activated carbon fiber and the potassium permanganate solution can be regulated, the uniformity of the reaction product is ensured, the formation of impurities is avoided, the purity of manganese dioxide is improved, and the activated carbon has a stable catalytic ability.

[0027] (3) In the present invention, the amine-containing compound is polyethyleneimine, the quinone-containing compound is 5-hydroxy-1,4-naphthoquinone, and the mixing mass ratio of the amine-containing compound to the quinone-containing compound is 1:1. Compared with the prior art, the amine-quinone network has a network structure, and the network structure can provide additional adsorption sites to enhance the adsorption capacity of small particles.

[0028] (4) In the present invention, before the activated carbon fiber reacts with the potassium permanganate solution, the activated carbon fiber is soaked in a NaOH solution to increase the active sites on the activated carbon fiber. Compared with the prior art, the number of active sites and micropores on the activated carbon fiber can be increased, and connection sites can be provided for manganese dioxide generated when the activated carbon fiber reacts with potassium permanganate, thereby improving the connectivity between the activated carbon fiber and manganese dioxide, enhancing the catalytic effect of manganese dioxide on the activated carbon fiber, and making the activated carbon fiber have better adsorption capacity.

[0029] (5) In the present invention, the concentration of the KMnO4 aqueous solution is 0.03M-0.07M, and the oven temperature is 100°C-140°C, so that when the potassium permanganate solution reacts with the activated carbon fiber, the type of manganese dioxide generated can be guaranteed. Compared with the prior art, the generation of δ-MnO2 on the activated carbon fiber is guaranteed, the catalytic performance of the activated carbon fiber is improved, the adsorption catalytic ability of the activated carbon fiber to formaldehyde is improved, and the removal rate of formaldehyde is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 is a method step diagram of a preferred embodiment of the present invention;

[0032] Figure 2 is a schematic diagram of an air filter material according to a preferred embodiment of the present invention;

[0033] In the figure, ①: protective layer, ②: particle filtration layer, ③: formaldehyde removal / antibacterial functional layer, ④: skeleton layer. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0036] like Figure 1 As shown, a method for preparing a formaldehyde adsorbing antibacterial material using activated carbon as a carrier comprises the following steps:

[0037] S1: soaking the activated carbon fiber in an alkaline solution, taking it out, washing it, and then drying it to obtain a modified activated carbon fiber, soaking the modified activated carbon fiber in a KMnO4 aqueous solution for 1 hour, and then placing the activated carbon fiber and the KMnO4 aqueous solution in a reactor to react for 24 hours;

[0038] S2: taking out the activated carbon fiber in the reactor in S1 and washing it, and then drying it in an oven for 12 hours at a temperature of 100° C. to 140° C. to obtain a formaldehyde adsorbing activated carbon material;

[0039] S3: mixing the amine-containing compound and the quinone-containing compound for reaction for 1-2 hours to form an aminequinone network, preparing the aminequinone network into an aminequinone network solution, soaking the formaldehyde adsorption activated carbon material in S2 into the aminequinone network solution for 2-4 hours, taking out the material after soaking and drying it at room temperature for 12-16 hours to obtain a primary treatment adsorption material;

[0040] S4: adding the once treated adsorption material in S3 into the silver solution and stirring for 4 hours, drying and heating the solid matter to obtain a formaldehyde adsorption antibacterial material with activated carbon as a carrier.

[0041] The alkaline solution in S1 can be a NaOH solution with a concentration of 1M. The activated carbon fiber is immersed for 30 minutes, and the activated carbon fiber is cleaned before immersion. Alkali treatment can introduce more oxygen-containing functional groups, such as hydroxyl and carboxyl groups, on the surface of the activated carbon fiber. These functional groups can react with potassium permanganate to increase the active sites on the surface of the activated carbon fiber, thereby improving its chemical adsorption capacity for small particles. Alkali treatment can remove impurities and blockages on the surface of the activated carbon fiber, thereby increasing its porosity and specific surface area. This provides more space for the penetration and distribution of potassium permanganate, which helps to improve the adsorption performance of the material. The surface of the activated carbon fiber after alkali treatment carries a negative charge, which helps to attract and fix the MnO4- ions in potassium permanganate, promote the occurrence of redox reactions, and thus form more active manganese oxides on the surface of the activated carbon fiber.

[0042] The concentration of KMnO4 aqueous solution in which the modified activated carbon fiber is soaked is 0.03M-0.07M. During the KMnO4 modification process, active sites are formed on the surface of the activated carbon fiber, which have strong adsorption and catalytic oxidation capabilities for small particles. KMnO4 modification will increase the specific surface area of ​​the activated carbon fiber, thereby providing more physical adsorption sites and enhancing the adsorption capacity for small particles. KMnO4 modification will change the pore structure of the activated carbon fiber, increase the proportion of micropores, and thus improve the adsorption capacity for small particles. The concentration of KMnO4 aqueous solution is 0.03M-0.07M, and the oven temperature is 100℃-140℃, so that when the potassium permanganate solution reacts with the activated carbon fiber, it can ensure the type of manganese dioxide generated, ensure the generation of δ-MnO2 on the activated carbon fiber, and improve the catalytic performance of the activated carbon fiber, thereby improving the adsorption and catalytic ability of the activated carbon fiber for formaldehyde and improving the removal rate of formaldehyde.

[0043] δ-MnO2 has more oxygen vacancies than other crystalline phases of manganese dioxide. These oxygen vacancies not only reduce the adsorption energy of gas molecules, making formaldehyde and oxygen more easily adsorbed on the catalyst surface, but also promote the progress of various elementary reactions, thereby improving the catalytic oxidation efficiency of formaldehyde. The Mn-O bond of δ-MnO2 is relatively weak, which makes its surface lattice oxygen and surface adsorbed oxygen more active. This strong activity is conducive to the adsorption and activation of formaldehyde molecules on the catalyst surface, thereby promoting the catalytic oxidation of formaldehyde. In contrast, manganese dioxide in other crystalline phases has a weaker catalytic oxidation ability for formaldehyde due to its strong Mn-O bond and low activity of surface lattice oxygen and adsorbed oxygen. Formaldehyde molecules are adsorbed on the catalyst surface and activated to form an intermediate product methylenedioxy (DOM), which is oxidized by surface lattice oxygen and surface adsorbed oxygen to form formate species, which are further oxidized to carbon dioxide and water. In this process, the highly active surface lattice oxygen and adsorbed oxygen of δ-MnO2 play a key role.

[0044] The amine-containing compound in S3 is polyethyleneimine, the quinone-containing compound is 5-hydroxy-1,4-naphthoquinone, and the mixing mass ratio of the amine-containing compound to the quinone-containing compound is 1:1. Polyethyleneimine is a polymer with rich amino groups, and 5-hydroxy-1,4-naphthoquinone is a compound containing quinone groups. These two compounds can form a stable amine-quinone network through Schiff base reaction. This network structure can provide additional adsorption sites and enhance the adsorption capacity for small particles. The amine-quinone network has certain antibacterial activity because quinone compounds can interfere with the respiratory chain of bacteria, while amine compounds can destroy the cell wall of bacteria. This antibacterial property is particularly important for air filter materials because it can reduce the number of bacteria and viruses passing through the filter material.

[0045] The solvent of the amine quinone network solution in S3 is dimethyl sulfoxide, and the concentration of the amine quinone network solution is 0.03-0.05M. Dimethyl sulfoxide is a polar solvent that can dissolve a variety of organic substances, including amines and quinone compounds. This helps to form a uniform amine quinone network solution, thereby forming a uniform coating on the surface of the activated carbon fiber and enhancing the adsorption capacity for small particles. The uniform distribution of the amine quinone network on the surface of the activated carbon fiber can provide more adsorption sites and enhance the adsorption capacity for small particles. Silver ions and amine quinone networks may attack bacteria through different mechanisms, resulting in a synergistic antibacterial effect. Silver ions can penetrate the bacterial cell wall, react with proteins and enzymes in the cell, and inhibit their activity, while amine quinone networks may form a barrier outside the cell to prevent the growth and reproduction of bacteria.

[0046] The solid material drying and heating process in S4 is to separate the solid material and dry it at 100℃ for 1h and then heat treat it at 400℃ for 5h. The drying process at 100℃ helps to remove moisture and residual volatile organic matter in the material. This not only helps to improve the adsorption performance of the material because it reduces the competitive adsorption of moisture, but also helps to prevent expansion or rupture caused by moisture during subsequent high-temperature treatment. The heat treatment at 400℃ can further enhance the thermal stability of the material. Heat treatment can strengthen the chemical bonds in the material and improve its heat resistance and structural stability. High-temperature heat treatment can activate the adsorption sites on the surface of the material and increase its adsorption capacity for small particles. At high temperatures, some functional groups on the surface of the material will rearrange or form new active sites, thereby improving the adsorption performance. High-temperature heat treatment also helps to enhance the antibacterial properties of the material. At high temperatures, the antibacterial components in the material can be better dispersed and fixed on the surface of the material, thereby improving its antibacterial effect.

[0047] The reaction between the activated carbon fiber and the potassium permanganate solution in the reactor is a closed space reaction, which promotes the reaction between the activated carbon fiber and the potassium permanganate solution, and can control the temperature and pressure of the reaction, and can regulate the reaction process of the activated carbon fiber and the potassium permanganate solution, thereby ensuring the uniformity of the reaction products, avoiding the formation of impurities, improving the purity of manganese dioxide, and having stable activated carbon catalytic ability.

[0048] The reaction temperature in the reactor in S2 is 60°C. The reaction temperature in the reactor is 60°C, which allows the activated carbon fiber to react with potassium permanganate in a relatively low temperature environment, so that the activated carbon molecules and potassium permanganate can generate preliminary products, making the reaction process more gentle. The reaction equation is:

[0049] The preparation process of the silver solution in S4 is to dissolve AgNO3 in ammonia water, the mass fraction of AgNO3 in the silver solution is 0.5%, the concentration of ammonia water is 28wt.%, and the mass ratio of the formaldehyde adsorbed activated carbon material to the silver solution is 1: 100. Manganese dioxide as a catalyst can catalyze the antibacterial ability of silver nanomolecules, making it have a stronger antibacterial effect.

[0050] In order to achieve the above-mentioned purpose, the second technical solution adopted by the present invention is: a formaldehyde adsorption antibacterial material using activated carbon as a carrier.

[0051] like Figure 2 As shown, in order to achieve the above-mentioned purpose, the third set of technical solutions adopted by the present invention is: an air filtration material, which includes: a protective layer ①, a particulate filter layer ②, a formaldehyde removal / antibacterial functional layer ③ and a skeleton layer in sequence according to the airflow penetration direction, and the protective layer ①, the particulate filter layer ②, the formaldehyde removal / antibacterial functional layer ③ and the skeleton layer ④ are compounded by ultrasound.

[0052] The material of protective layer ① is PET spunbond non-woven fabric with a gram weight of 15-25g / m 2 The particle filter layer ② is made of PP melt-blown cotton with a gram weight of 25-40g / m 2 The material used for the formaldehyde removal / antibacterial functional layer ③ is a formaldehyde adsorption antibacterial material with activated carbon as the carrier, with a gram weight of 50-100g / m 2 The skeleton layer ④ is made of PET wet-laid non-woven fabric with a gram weight of 70-100g / m 2 .

[0053] Embodiment 1

[0054] This embodiment provides a formaldehyde adsorption antibacterial material using activated carbon as a carrier, and the preparation method is as follows:

[0055] S1: soaking the activated carbon fiber in a NaOH solution with a concentration of 1 M for 30 min, taking it out, washing it, and then drying it to obtain a modified activated carbon fiber, soaking the modified activated carbon fiber in a KMnO4 aqueous solution for 1 h, placing the activated carbon fiber and the KMnO4 aqueous solution in a reactor to react for 24 h, and the concentration of the KMnO4 aqueous solution in which the modified activated carbon fiber is soaked is 0.05 M;

[0056] S2: taking out the activated carbon fiber in the reactor in S1 and washing it, and then placing the activated carbon fiber in an oven for drying for 12 hours at a temperature of 120° C. to obtain a formaldehyde adsorbing activated carbon material;

[0057] S3: Mix polyethyleneimine and 5-hydroxy-1,4-naphthoquinone at a mass ratio of 1:1 for 2 hours to form an amine quinone network, prepare the amine quinone network solution from the amine quinone network solution, wherein the solvent of the amine quinone network solution is dimethyl sulfoxide, and the concentration of the amine quinone network solution is 0.02M, and soak the formaldehyde adsorption activated carbon material in S2 in the amine quinone network solution for 2-4 hours, take out after soaking and dry at room temperature for 12-16 hours to obtain a once-treated adsorption material;

[0058] S4: adding the once treated adsorption material in S3 into the silver solution, the preparation process of the silver solution is to dissolve AgNO3 in ammonia water, the mass fraction of AgNO3 in the silver solution is 0.5%, the concentration of ammonia water is 28wt.%, the mass ratio of formaldehyde adsorption activated carbon material to silver solution is 1:100, and stirring is carried out for 4h, the solid matter is separated and dried at 100℃ for 1h and then heat treated at 400℃ for 5h to obtain the formaldehyde adsorption antibacterial material with activated carbon as the carrier.

[0059] Embodiment 2

[0060] In this embodiment, the concentration of the quinone network solution in S3 is 0.03M, and the rest is consistent with the first embodiment.

[0061] Embodiment 3

[0062] In this embodiment, the concentration of the quinone network solution in S3 is 0.04 M, and the rest is consistent with the first embodiment.

[0063] Embodiment 4

[0064] In this embodiment, the concentration of the amine quinone network solution in S3 is 0.05M, and the rest is consistent with the embodiment 1.

[0065] Embodiment 5

[0066] In this embodiment, the concentration of the quinone network solution in S3 is 0.06 M, and the rest is consistent with the first embodiment.

[0067] The formaldehyde adsorption antibacterial materials in Examples 1 to 5 were subjected to particle adsorption rate and antibacterial rate experiments, and the experimental results are shown in Table 1:

[0068] Table 1 Experimental results of particle adsorption rate and antibacterial rate in Examples 1 to 5

[0069] Sample source Particle adsorption rate (%) Antibacterial rate (%) Embodiment 1 95.74 91.76 Embodiment 2 96.35 92.36 Embodiment 3 97.46 93.96 Embodiment 4 96.89 93.01 Embodiment 5 95.97 92.84

[0070] It can be seen from Table 1 that the particle adsorption rate and antibacterial rate of Examples 1 to 9 are greater than the particle adsorption rate and antibacterial rate in Comparative Example 1. The preparation method of formaldehyde adsorption antibacterial material in this application can effectively improve the particle adsorption capacity and antibacterial ability of the material.

[0071] In embodiments one to five, as the concentration of the amine quinone network solution gradually rises, the numerical values ​​of the particle adsorption rate and the antibacterial rate first increase and then decrease, because the amine quinone network forms a chemical bond with the activated carbon fiber through its amine group, increases the surface functional groups of the activated carbon fiber, thereby improving its adsorption capacity to harmful substances such as formaldehyde. As the concentration of the amine quinone network solution increases, more amine groups react with the activated carbon fiber, increasing the adsorption sites of the activated carbon fiber, thereby improving the adsorption rate, and the silver ions in the silver solution combine with the amine quinone network to form a silver amine quinone complex with a stronger antibacterial effect. The introduction of silver ions can further improve the antibacterial properties of the material. Too high amine quinone network solution concentration causes excessive cross-linking on the surface of the activated carbon fiber, forming a thicker coating, which can block the pores of the activated carbon fiber and reduce its adsorption properties. Excessive cross-linking also affects the mechanical properties and stability of the material, thereby affecting its antibacterial properties. The best embodiment in embodiments one to five is embodiment three.

[0072] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a formaldehyde adsorbing antibacterial material using activated carbon as a carrier, characterized in that: The following steps are involved: S1: soaking the activated carbon fiber in an alkaline solution, taking it out, washing it, and then drying it to obtain a modified activated carbon fiber, soaking the modified activated carbon fiber in a KMnO4 aqueous solution for 1 hour, and then placing the activated carbon fiber and the KMnO4 aqueous solution in a reactor to react for 24 hours; S2: taking out the activated carbon fiber in the reactor in S1 and washing it, and then drying it in an oven for 12 hours at a temperature of 100° C. to 140° C. to obtain a formaldehyde adsorbing activated carbon material; S3: mixing the amine-containing compound and the quinone-containing compound for reaction for 1-2 hours to form an aminequinone network, preparing the aminequinone network into an aminequinone network solution, soaking the formaldehyde adsorption activated carbon material in S2 into the aminequinone network solution for 2-4 hours, taking out the material after soaking and drying it at room temperature for 12-16 hours to obtain a primary treatment adsorption material; S4: adding the once treated adsorption material in S3 into the silver solution and stirring for 4 hours, drying and heating the solid matter to obtain a formaldehyde adsorption antibacterial material with activated carbon as a carrier.

2. The method for preparing a formaldehyde adsorbing antibacterial material with activated carbon as a carrier according to claim 1, characterized in that: The alkaline solution in S1 can be a NaOH solution with a concentration of 1 M. The activated carbon fiber is immersed for 30 minutes, and the activated carbon fiber is cleaned before immersion.

3. The method for preparing a formaldehyde adsorbing antibacterial material with activated carbon as a carrier according to claim 1, characterized in that: The reaction temperature in the reactor in S1 is 60°C.

4. The method for preparing a formaldehyde adsorbing antibacterial material with activated carbon as a carrier according to claim 1, characterized in that: The concentration of the KMnO4 aqueous solution in which the modified activated carbon fiber is immersed is 0.03M-0.07M.

5. The method for preparing a formaldehyde adsorbing antibacterial material with activated carbon as a carrier according to claim 1, characterized in that: The amine-containing compound in S3 is polyethyleneimine, the quinone-containing compound is 5-hydroxy-1,4-naphthoquinone, and the mixing mass ratio of the amine-containing compound to the quinone-containing compound is 1:

1.

6. The method for preparing a formaldehyde adsorbing antibacterial material with activated carbon as a carrier according to claim 1, characterized in that: The solvent of the amine quinone network solution in S3 is dimethyl sulfoxide, and the concentration of the amine quinone network solution is 0.01-0.1M.

7. The method for preparing a formaldehyde adsorbing antibacterial material with activated carbon as a carrier according to claim 1, characterized in that: The preparation process of the silver solution in S4 is to dissolve AgNO3 in ammonia water, the mass fraction of AgNO3 in the silver solution is 0.5%, the concentration of ammonia water is 28wt.%, and the mass ratio of the formaldehyde adsorbing activated carbon material to the silver solution is 1:

100.

8. The method for preparing a formaldehyde adsorbing antibacterial material with activated carbon as a carrier according to claim 1, characterized in that: The solid matter drying and heating process in S4 is to separate the solid matter and dry it at 100° C. for 1 hour and then heat treat it at 400° C. for 5 hours.

9. A formaldehyde adsorption antibacterial material with activated carbon as carrier, characterized in that: It is prepared based on the preparation method of a formaldehyde adsorbing antibacterial material using activated carbon as a carrier according to any one of claims 1-8.

10. An air filter material, characterized in that: The layers include, in order of airflow penetration direction: a protective layer, a particle filter layer, a formaldehyde removal / antibacterial functional layer and a skeleton layer, wherein the protective layer, the particle filter layer, the formaldehyde removal / antibacterial functional layer and the skeleton layer are compounded by ultrasound; The protective layer is made of PET spunbonded non-woven fabric with a gram weight of 15-25g / m 2 ; The particle filter layer is made of PP melt-blown cotton with a gram weight of 25-40g / m 2 ; The material used in the formaldehyde removal / antibacterial functional layer is a formaldehyde adsorption antibacterial material with activated carbon as a carrier as claimed in claim 9, with a gram weight of 50-100 g / m 2 ; The skeleton layer is made of PET wet non-woven fabric with a gram weight of 70-100g / m 2 .